The Effect of Structured Education Based on Midwifery Care on Anxiety Levels Among Premenopausal Cervical Cancer Patients - Sari Wulan Asih; Sara Nurmala; Dyah Ayu Septika Wijaya; Novita Sari; Eka Herlina (Global Health Science Group, 2026)
Premenopausal women with cervical cancer experience heightened anxiety due to hormonal changes, fear of treatment, and uncertainty about their future roles. Estrogen decline during perimenopause reduces neurotransmitter levels, further increasing vulnerability to anxiety. This study aimed to evaluate the effectiveness of structured education based on midwifery care in reducing anxiety levels among premenopausal cervical cancer patients at a public hospital in Banten. A quasi-experimental design with a one-group pretest–posttest approach was used. A total of 30 participants were selected through purposive sampling based on the following inclusion criteria: aged 35–50 years, diagnosed with cervical cancer, premenopausal status, and ability to communicate effectively. The dependent variable was anxiety level, measured using the validated Hospital Anxiety and Depression Scale–Anxiety (HADS-A). This instrument consists of 7 items, each scored on a 4-point Likert scale (0–3), with a total score ranging from 0 to 21, where higher scores indicate greater levels of anxiety. The Bahasa Indonesia version of the HADS-A was used, which has demonstrated good reliability with a Cronbach’s alpha of 0.82. Anxiety levels were assessed before and after the intervention. The structured educational intervention covered four key topics: understanding cervical cancer, perimenopausal changes, anxiety management techniques, and psychosocial and family support. Data were analyzed using a paired t-test, with statistical significance set at p < 0.05. After the intervention, the proportion of respondents with normal anxiety levels increased from 16.7% to 46.7%, while severe anxiety decreased from 16.7% to 0%. The mean anxiety score significantly decreased from 12.40 to 8.10 (p < 0.05). Structured education grounded in midwifery care offers a holistic, woman-centered approach that has the potential to effectively alleviate anxiety in this vulnerable.